Radical-mediated divergent cyclization of benzamides toward perfluorinated or cyanated isoquinolinediones. Issue 39 (15th September 2016) - Deng, You-Lin; Tang, Shi; Ding, Guo-Liang; Wang, Ming-Wei; Li, Jie; Li, Zeng-Zeng; Yuan, Li; Sheng, Rui-Long
Abstract : A simple and efficient copper-controlled divergent cyclization of benzamides, which leads to perfluorinated or cyanated isoquinolinediones, is developed. Abstract : A simple and efficient copper-controlled divergent cyclization of benzamides, which leads to perfluorinated or cyanated isoquinolinediones, is developed. In the presence of AIBN, methacryloyl benzamides with perfluoroalkyl iodides undergo cascade radical addition/cyclization to afford perfluoroinated isoquinolinediones as the major product under metal-free conditions, whereas the use of CuI (10 mol%) is able to redirect the cyclization to yield isoquinolinediones bearing an α-cyano quaternary carbon center. The cyclization features controllable divergent synthesis and a broad substrate scope as well as highly practical reaction conditions, thereby making this strategy a highly attractive means to fluorinate or cyanate isoquinolinediones.